Real-time monitoring with iTLR4 assay identifies ligand-dependent TLR4-TLR4 conformational dynamics - Mustafa, Sanam; Evans, Samuel G.; Hutchinson, Mark R. (Frontiers in Immunology, 2025)
Toll-like receptor 4 (TLR4) plays a pivotal role in the innate immune system by recognizing pathogens and initiating immune responses. Despite extensive research over three decades, current methods lack the resolution to measure ligand-induced TLR4 receptor dynamics at the earliest stages of signaling, relying instead on downstream outputs such as gene expression and cytokine secretion. Here, we present the illuminating TLR4 (iTLR4) assay, a novel Bioluminescence Resonance Energy Transfer (BRET)-based platform that provides real-time insights into TLR4 receptor-level events in live cells. The iTLR4 assay demonstrates, for the first time, that lipopolysaccharide (LPS) induces stable interactions between intracellular domains of TLR4 monomers, with an EC50 of 660 EU/mL. Kinetic analysis revealed a gradual, sustained increase in the BRET signal over time. Additionally, the assay uncovered subtle mechanistic differences among functional antagonists. While all antagonists completely abolished LPS-induced IL-8 secretion, the assay demonstrated that at the receptor level LPS-RS completely inhibited the LPS-induced BRET signal, TAK-242 partially inhibited it and (+)-naloxone potentiated it. The assay also identified potential regulatory roles for CD14 and MD2 in naloxone stereoisomer activity, marking the first report of such mechanistic differences. These findings highlight the unique capabilities of the iTLR4 assay to track nuanced TLR4 receptor dynamics, enabling high-throughput screening of TLR4-specific modulators. This platform provides critical insights into ligand-induced signaling, paving the way for the development of novel therapeutics targeting TLR4-related diseases and advancing our understanding of innate immune responses.